Os surdos de Aracaju : observação do discurso cultural e identitário dentro do contexto social ouvinte - Oliveira, Daisy Mara Moreira de (2012)
This work is a field research with the deaf in Aracaju, from the observation of the speech of the leaders of the capital, where there are two terms that are thoroughly discussed extensively in anthropology, whether, culture and identity. Given this, we raise the following questions: what is the origin of this common discourse produced in the social circles of Sergipe deaf? What the place and meaning that the sign language occupies in what they call "culture and deaf identity" '. Once it was realized that this speech came from a larger context, we propose the following objective: the light of anthropology to observe the deaf from Aracaju to ascertain how they are adhering to the cultural discourse and national identity and are positioning themselves ahead of surrounding society. Thus, in the first chapter, we came to find out how to use the two terms in the trajectory of this minority, in appropriating the historiography because we believe that many images are carved through the literature and this can perpetuate itself even beyond national borders. Use of interdisciplinary areas related to authors, both deaf and hearing, are playing in the literature that a portrait of the deaf. In the second chapter we sought to identify the terms culture and identity are addressed by anthropologists, and whether or not they were used properly investigated by the community. And in the third chapter, using ethnography, we record the movements, meeting spaces and social practices that subject, where the emphasis was learned sign language as a major brand identity. What can we conclude from this research is that, due to the stereotypical treatment of this individual in the historical course was designed, socially speaking, an image of helpless. And this subject, not accepting the data labels, teamed up in favor of the reversal of this image. So have forged, reproduced terms that distinguished them from hearing society, and through the linguistic attribute demonstrated their distinct brand identity. We also understand that beyond the distinction between language and the deaf have different cultural elements of us listeners, such as how to name your subjects. And by that very condition of solitary confinement, when they are born into families that do not use pounds, lose much of that is transmitted orally, ie, there is a loss of cultural transmission in which the group is inserted. But once together with their peers is an identification and strengthening. We could say that the deaf not have a culture and identity, but cultures and identities.